A Comparative Study Of The Mean And Median Rainfall Patterns In Northwest Peninsular Malaysia. - Chan, Ngai Weng (1990)

(untitled)
Most rainfall studies in Malaysia have used the mean to represent the average rainfall characteristics of the respective regions under study.